Development Of Agricultural Culture In The Irrigation System Of The Northern And Central Regions Of The Surkhandarya Oasis - Choriev Nuriddin Khushbokovich (Genius Journals, 2022)
Viticulture is another important branch of horticulture in the northwestern part of Boysun and Denau, as well as in the mountainous regions of Sherabad, Sariosiya, Uzun, in the foothills and foothills of Kohitang and Boysuntag, in the Gissar and foothills of the Bukhara Emirate. Surkhan oasis was also famous for its sweet apricots. Vegetables such as onions, carrots, turnips, melons, watermelons, cucumbers, pumpkins (kadi), melons, tobacco and cotton are grown in the oasis. The Surkhan oasis has long been home to sweet and long-lasting melons: olapochok, aknovvot, kokcha, borikalla, amiri, zarkokil, chapcha, otkalla, tirish, kondalangtor. Olapochok and aknovvot melons were sent to the palace of the Emir of Bukhara
Keywords: artificial irrigation; sedentary population; hussaini; black raisins